2015
DOI: 10.3168/jds.2015-9371
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Reliability of single-step genomic BLUP breeding values by multi-trait test-day model analysis

Abstract: The purpose of our study was to develop an approximation procedure to estimate reliabilities of single-step genomic BLUP breeding values in a test-day model for routine evaluation of milk yield in a dairy cattle population. Input data consisted of 20,220,047 first-, second-, and third-lactation test-day milk yield records of 1,126,102 Czech Holstein cows (each lactation being considered a separate trait), with 1,844,679 animals in the pedigree file and with genomic data from 2,236 bulls. Evaluation was accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Higher EBV accuracies for RRGM than for RRPM (3.6% for 305-MY and 2.5% for 305-d FP) indicated that including genomic information in genetic evaluations increased prediction accuracies over genetic evaluations based only on pedigree and phenotypic data in this population. This agreed with results from previous research showing that utilization of genomic information in addition to pedigree and phenotypic information to evaluate dairy cattle yielded higher prediction accuracies in various dairy populations (VanRaden et al, 2009;Van Doormaal et al, 2009;Wiggans et al, 2011;Su et al, 2012;Thomasen et al, 2012;Bauer et al, 2014Bauer et al, , 2015Přibyl et al, 2014;Jattawa et al, 2015). Mean accuracies of 305-d MY genomic-polygenic EBV computed with single-step cumulative 305-d models were 7.2% higher than the mean accuracy from polygenic EBV in this same Thai population (Jattawa et al, 2015).…”
Section: Variance Components Heritabilities and Genetic Correlationssupporting
confidence: 93%
See 2 more Smart Citations
“…Higher EBV accuracies for RRGM than for RRPM (3.6% for 305-MY and 2.5% for 305-d FP) indicated that including genomic information in genetic evaluations increased prediction accuracies over genetic evaluations based only on pedigree and phenotypic data in this population. This agreed with results from previous research showing that utilization of genomic information in addition to pedigree and phenotypic information to evaluate dairy cattle yielded higher prediction accuracies in various dairy populations (VanRaden et al, 2009;Van Doormaal et al, 2009;Wiggans et al, 2011;Su et al, 2012;Thomasen et al, 2012;Bauer et al, 2014Bauer et al, , 2015Přibyl et al, 2014;Jattawa et al, 2015). Mean accuracies of 305-d MY genomic-polygenic EBV computed with single-step cumulative 305-d models were 7.2% higher than the mean accuracy from polygenic EBV in this same Thai population (Jattawa et al, 2015).…”
Section: Variance Components Heritabilities and Genetic Correlationssupporting
confidence: 93%
“…Mean accuracies of 305-d MY genomic-polygenic EBV computed with single-step cumulative 305-d models were 7.2% higher than the mean accuracy from polygenic EBV in this same Thai population (Jattawa et al, 2015). Similarly, prediction accuracy for 305-d MY from a single-step random regression genomic-polygenic model was 6.8% higher than that from random regression polygenic evaluation in a population of 1,854,275 Czech Holstein using 40,653 SNP from 2236 genotyped sires (Bauer et al, 2015). This 6.8% increase in accuracy was higher than the value of 3.6% obtained here although the number of genotyped animals was smaller than the 2661 animals genotyped in this Thai population.…”
Section: Variance Components Heritabilities and Genetic Correlationsmentioning
confidence: 57%
See 1 more Smart Citation
“…The accuracy of predictions from the ssGBLUP method was better than that obtained with the BLUP method, with 32-54% for the ratio of accuracy and 60-80% for the methods. The accuracy values in this study were similar to those previously obtained [63,64]. Low accuracies can occur for a number of reasons: (1) A small reference population (number of animals with genotype data); therefore, the reference population should be greater than 1000 to significantly increase the accuracy [64].…”
Section: Accuracysupporting
confidence: 87%
“…Increase of R 2 in later lactations may be caused by the genetic evaluation model considered genetic correlation among lactations. Bauer et al () reported that the approximated reliability of GEBV for genotyped young bulls by ssGBLUP with multiple‐trait test‐day model between the first three lactations was highest in the second lactation. An implementation of the multiple‐trait model improved R 2 of the trait with a limited number of records (Guo et al ; Bauer et al ).…”
Section: Resultsmentioning
confidence: 99%